Low‐level lysosomal membrane permeabilization for limited release and sublethal functions of cathepsin proteases in the cytosol and nucleus - Thomas Reinheckel; Martina Tholen (FEBS Open Bio, 2022)
For a long time, lysosomes were purely seen as organelles in charge of garbage disposal within the cell. They destroy any cargo delivered into their lumen with a plethora of highly potent hydrolytic enzymes, including various proteases. In case of damage to their limiting membranes, the lysosomes release their soluble content with detrimental outcomes for the cell. In recent years, however, this view of the lysosome changed towards acknowledging it as a platform for integration of manifold intracellular and extracellular signals. Even impaired lysosomal membrane integrity is no longer considered to be a one‐way street to cell death. Increasing evidence suggests that lysosomal enzymes, mainly cathepsin proteases, can be released in a spatially and temporarily restricted manner that is compatible with cellular survival. This way, cathepsins can act in the cytosol and the nucleus, where they affect important cellular processes such as cell division. Here, we review this evidence and discuss the routes and molecular mechanisms by which the cathepsins may reach their unusual destination.